Program â€œGerakan Subuh Mengajiâ€ Episode 152 â€œPendidikan Lingkungan Hidup Pada Anak Dan Remajaâ€ Di TVmu Dalam Menjalankan Fungsi Pendidikan - Nurul Hana Aprilia; Makroen Sanjaya (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Currently, only a small amount of local television in Indonesia is operating as a teaching medium due to a close rivalry amongst local broadcasters. According to current thinking, functions of menghiburlah are more prevalent in television media, thus there is only a small amount of local television that airs programs with educational goals. To understand how TVMu performs its function of education through the program